Brincando e aprendendo com o uso do conhecimento popular das plantas medicinais com os alunos das series iniciais da escola Nossa senhora do Perpetuo Socorro na comunidade do rio Arapapu - VILHENA, Maria do Socorro Silva de (2024)
The study aimed to raise the interest of students about the use of medicinal plants as alternative medicine and the preservation of traditional knowledge, and identify three species of medicinal plants commonly used in the Arapapu river community with detailed information about the lemongrass (Melissa officinalis), rue (Ruta graveolens) and mint (Mentha piperita). To recognize the importance of traditional knowledge of the families of students and understand the different uses and purposes in a playful manner within the school context. For this purpose, a qualitative research was carried out through participant observation with data collected from structured interviews, informants were three students of the classes of the 2nd and 3rd year of the School Our Lady of Perpetual Help in Rio Arapapu, for you to see how occurs learning by use of the medicinal plants. In this work it was used as methodological resource structured interviews. It verified - that students who participated in the educational workshop on medicinal plants, could learn and value the use of plants and their chemical advantages to continue taking them as a means to cure their diseases, taking advantage of the diversity of ways that nature offers us . Playing In conclusion, the students learned to value the popular knowledge of medicinal plants adding their learning relevant information in support of the cultural revival of these plants at the Rio Arapapu community.